Walory przyrodnicze gminy Uniejów – formy ochrony przyrody - Smętkiewicz, Katarzyna Maria; Smętkiewicz, Karolina Katarzyna (Biuletyn Uniejowski, 2012)
This contribution describes the quality of the natural environment and landscape of Uniejów municipality and the state of their preservation. An extensive stock-taking in respect of nature protection forms was carried out on the territory of this municipality. It identified 9 protected and endangered habitats as listed in Appendix I to the Habitat Directive and 6 nature protection forms, such as Nature 2000 area, protected landscape area or nature monument. Valorisation of the different parts of the municipality resulted in updating the knowledge about its natural and tourist values. Research findings confirm the diversity and attractiveness of the natural environment of this region. It is important to place emphasis on preservation of the existing natural assets and introduction of new forms of nature protection.